Inventories as Factors of Production and Economic Fluctuations - Ramey, Valerie A. (American Economic Review, 1989)
This paper presents a theory of inventory investment by stage-of-processing, and uses it to examine the role of inventory investment in economic fluctuations. Three conclusions emerge from the estimation. First, the estimates generally satisfy the theoretical restrictions. Second, the elasticity of inventory demand with respect to output is high, indicating an important accelerator effect. Finally, the estimates suggest that shifts in the demand for inventories are an important source of economic fluctuations.